Analisis Ketahanan Nasional Dalam Dinamika Tren Dan Persaingan Food And Beverage Cafe Pada Sektor Ekonomi Kreatif Dan Pangan: Studi Observasi Di Elkafe Kediri - Fajar Setyowati; Lunna Azzahra Wibisono; Eka Nirmala Febriya; Jassieka Deby Arrahma; Kresinia Novitasari (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The rapid growth of the food and beverage (F&B) industry in urban areas presents both substantial opportunities and distinct threats to national resilience, particularly within the creative economy and food sectors. This study explores how local MSMEs navigate intensive market competition and changing consumer trends to sustain economic stability. Focusing on Elkafe Kediri, a prominent café established in December 2025,  This study employs a qualitative descriptive approach specifically a case study design as it focuses on an in-depth analysis of a single subject: Elkafe Kediri. Through this approach, the researcher is able to gain a comprehensive overview of the strategies implemented by Elkafe to navigate competition within the food and beverage industry. Research data were obtained through direct observation and in depth interviews with the Operations Manager of Elkafe Kediri.The findings demonstrate that Elkafe maintains economic resilience through dual-track career and marketing strategies (inbound and outbound), human resource optimization facing severe local competition, and strategic supply chain localization. Challenges including human resource competition and mass-marketing demands are managed via structured service quality improvement and strong cafe branding. This localized economic viability contributes directly to national resilience by securing local employment, stabilizing regional food supply distribution, and fostering the creative economy ecosystem in Kediri.